Making volunteering visible - Uttam Singh, Surjit Singh; Md. Sail, Rahim; Abu Samah, Bahaman; Tajuddin Shah, Raja Ahmad; Lumayag, Linda Alfarero (Universiti Putra Malaysia Press, 2005)
Volunteer work is always associated with free and unpaid employment and is never accounted for in the national data of Malaysia. This paper argues that voluntary work should be made visible by according it with economic value for it to be part of the national asset of the country. The empirical basis of this paper is reflected in a research survey conducted in 2003 on the tangible and intangible contributions of the public service retirees who belonged to the Professional and Managerial group within the Malaysian civil service. It is premised on the belief that providing a decent and liveable monetary value to the retirees' voluntary contribution in community development would usher in more retirees to come forward to engage in meaningful and productive work during the so-called transition period of their waking life.